A new species of the genus Paravillersia (Acari: Prostigmata: Stigmaeidae) from Western Siberia, with supplementary description of Paravillersia grata Kuznetsov, 1978 - Khaustov, Alexander A. (Zootaxa, 2014)
A new species of the genus Paravillersia Kuznetsov, 1978 (Acari: Stigmaeidae), P. jamaliensis Khaustov sp. nov. is described from mosses on fen in Western Siberia, Russia. The supplementary description of Paravillersia grata Kuznetsov, 1978 is provided based on the type material.